2016
DOI: 10.2486/indhealth.2015-0112
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health scenario of Indian informal sector

Abstract: Workers in the Indian informal sector are engaged with different occupations. These occupations involve varied work related hazards. These occupational hazards are a consequent risk to health. The study aimed to determine occupational health scenario in the Indian Informal sector. One thousand eleven hundred twenty two workers from five different occupations namely weaving (handloom and power loom), construction, transportation, tobacco processing and fish processing were assessed by interviewer administered h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 36 publications
2
36
1
1
Order By: Relevance
“…Spine pain is a major musculoskeletal burden occurring at a high rate of 42% in India. 4 We observed that ~ 43.5% of dancers practicing classical Indian dance (50% were Bharatanatyam dancers) suffer from low back pain. 5 Mullerpatan et al report novel findings on gait kinematics in Bharatanatyam dancers presenting with low back pain.…”
Section: VImentioning
confidence: 93%
“…Spine pain is a major musculoskeletal burden occurring at a high rate of 42% in India. 4 We observed that ~ 43.5% of dancers practicing classical Indian dance (50% were Bharatanatyam dancers) suffer from low back pain. 5 Mullerpatan et al report novel findings on gait kinematics in Bharatanatyam dancers presenting with low back pain.…”
Section: VImentioning
confidence: 93%
“…Penelitian lain menyatakan bahwa kelelahan kerja ditandai oleh penurunan efisiensi dalam pekerjaan, ketrampilan dan meningkatkan kebosanan dan kecemasan (Saftarina, Mayasari, & Vilia, 2018). Para pekerja sering mengalami ketidaknyamanan pada system musculoskeletal dan gangguan kesehatan lain (Nag, Vyas, & Nag, 2016).…”
Section: Hasil Dan Pembahasanunclassified
“…International studies indicate that uneducated men are more likely to experience fatal automobile crashes than more highly educated men and also asserts that the rate of serious non-fatal injury is higher for individuals of lower education levels, but less serious injury is not so clearly correlated with education [21].…”
Section: Knowledge On Preventive Measures Of Occupational Safety Andmentioning
confidence: 99%